Prevalence of work related upper limb disorders and the associated psychosocial factors among midwives. (2021) - Kacem, I.; Boughattas, W.; Ghardallou, M.; Maoua, M.; Hafsia, M.; Ben Ahmed, M.; Kalboussi, H.; Ajmi, T.H.; Chatti, S.; El Maalel, O.; Kahloul, M.; Mrizak, N.
Abstract: Background: Work related upper limb disorders (WRULDs) are a major occupational health concern. The health field, with its various occupational categories, is a conducive environment for the emergence of these conditions. Midwives are particularly at risk for WRULDs. Objective: To determine the prevalence of WRULDs among midwives exersing at a Tunisian academic maternity and identify its associated factors. Methods: This is a cross-sectional descriptive study conducted among midwives working at the maternity Departement of the Farhat Hached Teaching Hospital in the central region of Tunisia, during the period from March to May 2016. This study was based on a self-administered questionnaire including socio-professional characteristics, the "Nordic" questionnaire for the assessment of WRULDs in the last 12 months and the last 7 days, and the job content questionnaire for the evaluation of the psychosocial environment at work. Results: A total of 54 midwives participated to our study with a response rate of 84.3%. The mean age was 46.1 + 8.7 years. In the last week before the study, the median number of deliveries performed by midwives per day was 3. Job strain was noted in 33.3% of cases. During the last 12 months, the prevalence of WRULDs was 90.7%. The complaints were located at the neck in 72.7% of cases. For the last seven days, this prevalence was 53.7%. Obesity and upper limb trauma history were significantly associated with WRULDs over the last 7 days. No social-occupational risk factors were associated with WRULDs in midwives in the last 12 months. Conclusion: Our study found a high prevalence of WRULDs in midwives, emphasizing the need of adequate prevention in order to reduce the importance of this occupational disease and its harmful consequences.